Lactic-Acid Bacteria Supplement Fermented Dairy Products with Human Behavior-Modifying Neuroactive Compounds - Alexander V. Oleskin; Olga G. Zhilenkova; Boris A. Shenderov; Adelaide M. Amerhanova; Vladimir S. Kudrin; Peter M. Klodt (Journal of Pharmacy and Nutrition Sciences, 2014)
Using high performance liquid chromatography, we established that probiotic Lactobacillus strains (Lactobacillus helveticus 100ash, L. helveticus NK-1, L. casei K3III24, and L. delbrueckii subsp. bulgaricus) grown on two milk-containing nutrient media produce important neuromediators such as biogenic amines, their precursors and deamination products, as well as neuroactive amino acids. The concentrations of biogenic amines (such as catecholamines and, with L. helveticus 100ash, also serotonin) equal or exceed those contained in the bloodstream of healthy adult humans, whereas those of most amino acids are comparatively low, except for gamma-aminobutyric acid (GABA). Of paramount importance is the fact that the bacterial cultures can release micromolar amounts of GABA and L-3,4-dihydroxyphenylalanine (DOPA)into the milk-containing media. It is known that DOPA passes through the gut-blood and the blood-brain barrier and converts into major neurotransmitters (dopamine and norepinephrine) that influence important aspects of human behavior. The data obtained suggest that dairy products fermented by live lactobacilli-containing starters are potential sources of human behavior-modifying substances.